Bushen Culuan Decoction Ameliorates Premature Ovarian Insufficiency by Acting on the Nrf2/ARE Signaling Pathway to Alleviate Oxidative Stress - Chen, Yanxia; Fan, Xiaodi; Ma, Kun; Wang, Kaili; Tian, Caidie; Li, Min; Gong, Linjuan (Frontiers in Pharmacology, 2022)
Premature ovarian insufficiency (POI) can result in lower fertility and shorten the female reproductive span. Bushen-Culuan Decoction (BCD) is a traditional Chinese medication utilized for treating POI for many years. We previously observed that BCD protects against further deterioration of the ovarian reserve of POI patients, however, the underlying mechanism has not been well studied. Our investigation seeks to evaluate the effect of BCD on POI induced by Tripterygium wilfordii polyglycosidium (TWP) and the likely mechanistic pathways, which we hypothesize may involve the Nrf2/ARE pathway. The body weights, estrous cycle, serum hormone levels, histological follicular analysis and quantification, levels of oxidative stress biomarkers in the ovarian tissue of POI mice models were evaluated. Western blotting and RT-PCR enabled quantification of the components of the Nrf2/ARE pathway. Our results showed that BCD restored hormonal profiles and estrous cycles of POI mice similar to those observed in healthy controls. BCD reduced the numbers of atretic follicles while increasing the number of primordial follicles. BCD facilitated lower 8-OHdG and MDA levels while increasing levels of key antioxidant enzymes including GSH-Px, CAT, and SOD. Furthermore, TWP increased Bach 1, Nrf2 and Keap 1 expressions at the translational level, while decreased those of HO-1. BCD treatment also promoted nuclear translocation rates of Bach 1 and Nrf2, suppressed Keap 1 protein expression, as well as raised HO-1 protein expression. Taken together, BCD likely augments ovarian reserve by activating the Nrf2/ARE signaling pathway, which stimulated higher levels of antioxidants and suppressed oxidative stress. BCD may be an important therapeutic compound in POI.